Reorganization of Traditional Medicine Regulation Within the National Health System from A Legal Pluralism Perspective to Address Disharmonization of Laws and Regulations - Agung Suhirman; Muharyati Muharyati; Latifah Indriasari Utami; Fajar Hadi Wijayanto; Marsudi Dedi Putra (Civiliza Publishing, 2026)
This study aims to analyze and formulate the restructuring of traditional medicine regulation within the national health system using a legal pluralism perspective to address the disharmonization of laws and regulations. This effort is undertaken to achieve legal certainty, public protection, and fair recognition of traditional practices. The research method employed is normative juridical, focusing on the analysis of legal norms, principles, and rules through statutory, theoretical, and doctrinal approaches. Data were collected through a literature review of primary, secondary, and tertiary legal materials, which were then analyzed qualitatively using legal interpretation and deductive reasoning. The regulation of traditional medicine currently has a strong foundation through Law Number 17 of 2023 on Health; however, significant normative disharmonization still exists. Regulatory conflicts are evident in the potential criminalization under the Criminal Code (KUHP) of non-medical practices deemed misleading, while the Health Law provides recognition of such practices. Formal standards established by the government tend to follow a modern medical paradigm, making them difficult for traditional practitioners—who rely on empirical experience and local wisdom—to fulfill. Protection of traditional knowledge as a collective right of indigenous communities has also not been adequately regulated within the national legal framework. An ideal regulatory restructuring requires synchronization among regulations and the adoption of legal pluralism principles so that the state legal system can accommodate customary law and social norms living within society. Certification mechanisms need to be made more inclusive by recognizing hereditary expertise, and supervision should be designed in a participatory manner involving local communities. Integrated harmonization will create a balance between the recognition of cultural identity and the assurance of safety for service users.